Usage of Online Public Access Catalogue (OPAC) by undergraduate students atSokoine University of Agriculture - Katabalwa, Anajoyce Samuel; Mnzava, Ester Ernest (University of Dar es Salaam Library Journal, 2021)
This study aims to examine the usage of Online Public Access Catalogue (OPAC) by undergraduate students atSokoine University of Agriculture (SUA). Specifically the study aimed to determine whether the undergraduate students were aware of OPACat Sokoine National Agricultural Library (SNAL), to examine the access to OPAC by undergraduate students at SNAL,to examine the usage of OPAC by undergraduate students at SNAL and to identify the challenges encountered by undergraduate students in the usage of OPAC at SNAL. The study involved 100 purposively selected Bachelor of Information and Records Management (BIRM) students.This cross-sectional study basically used self-administered questionnairesas data collectionmethod. The data were analysed with the aid of the Statistical Package for Social Sciences (SPSS). Findings of the study revealed that majority of respondents were aware of OPAC. The respondents used OPAC for various reasons including knowing the librarymaterialsavailable in the collection for a short time, locating library materials, and knowing the status of books €“ if they are available or on loan. OPAC are accessed from various points including in Library, Hostels,and study tables and seats made of cement locally known asvimbweta.Various ICT devices such as computers in the library, smartphones and laptops are used to access OPAC. However, some challenges such as lack of basic ICT skills, lack of training, power outage were found to be hindering the usage of OPAC. The study recommends provision of training to increase skills, increase marketing strategy and purchase of a heavy-duty automatic generator to solve the power outage challenge.